KEDUDUKAN INSTRUKSI PRESIDEN REPUBLIK INDONESIA NOMOR 1 TAHUN 1991 TENTANG PENYEBARLUASAN KOMPILASI HUKUM ISLAM DALAM SISTEM HUKUM KEWARISAN INDONESIA - Fajar Sugianto; Denny Ardhi Wibowo; Tomy Michael (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2020)
The Islamic inheritance law system is one of the inheritance law systems that apply in Indonesia. Presidential Instruction 1/1991 is a legal instrument that makes Islamic law a positive law in Indonesia, however, the development of the constitutional system and the legal system in Indonesia has undergone very rapid changes since the reform era. This raises new legal problems in the implementation of the Compilation of Islamic Laws considering that the position of Presidential Instruction 1/1991 in the statutory system is not known as statutory regulation.In the aspect of binding power, the Presidential Instruction cannot be applied to the public because it does not have general binding power and only binds inwardly against officials with a lower position in 1 (one) institution. Even so, the existence of Presidential Instruction 1/1991 is still recognized to this day considering that its substance was formed through a joint decision between the Minister of Religion and the Chief Justice of the Supreme Court. Thus, the Compilation of Islamic Law binds religious court judges who are under the environment of the Supreme Court. Judges can use the Compilation of Islamic Law as a legal basis for resolving disputes that occur between Muslim communities.